IMPLEMENTASI ALGORITMA KRIPTOGRAFI AES DALAM PENGAMANAN FILE TEKS - Pazrian Nurul Latip (Jurnal Riset Sistem Informasi, 2025)
In today's digital world, data security is crucial for communication and document storage, especially for text files containing sensitive information. The focus of this research is the use of modern cryptographic algorithms Advanced Encryption Standard (AES) in text file encryption. The research process includes the creation of a prototype application that uses (AES). After developing the prototype, we tested its performance both in terms of processing speed and security level. From there it is known: AES is much more efficient than Vigenère. Vigenère may have strong encryption, but unfortunately it is easily broken by cryptographic analysis.